The Application of Remote Sensing in Vegetation Cover, Sudan - Ahmed , Eisa M.; Hassan, El Gunaid F. (Cutting Edge Research in Biology Vol. 5, 2023)
This paper sought to review several studies on the use of remote sensing in Sudan with a focus on vegetation cover in various regions by many scholars; the integration of remote sensing in the gum Arabic belt; southern Gadarif region; ahable and wad grabou area, white Nile state with a focus on the assessment and mapping of land use land cover change through mapping and monitoring the changes that occurred in land use land cover, due to drought, climate change, and mismanagement; east of the Nile Khartoum State, and in the center during a half-century. Following are recommendations derived from these studies: the use of assessment indicators including NDVI, SAVI, and PCA –manipulated in color composite and/or unsupervised classification can be used as an appropriate mean for rangeland monitoring and assessment which was recommended from the study of North Kordofan state.